Enhancing tuberculosis case notifications through mapping sales of medicine in the private sector: a quasi-experimental study in Punjab province, Pakistan - Beatrice Kirubi; Kinz Ul Eman; Usman R. Lodhi; Razia K. Fatima; Ghulam Nabi Kazi; Tahmeena Tahmeena; Syed Karam Shah; Jacob Creswell (BMC Health Services Research)
Abstract Introduction In Pakistan, almost one-third of people who develop tuberculosis (TB) are missed by the National TB Program (NTP). A considerable number of people with TB receive treatment in the private sector but remain unnotified. This study documents the outcomes of an intervention to identify people with TB through private pharmacy engagement, building on mapping TB medicine sales in Punjab Province. Methods A comprehensive intervention was carried out in four districts of Punjab with high anti-TB drug sales, comprising a policy change requiring mandatory notification of TB medication sales, mapping and engaging pharmacies selling anti-TB drugs, reporting through a novel ‘eTB’ mobile application and providing support via a call center. We collected both historical and prospective TB notification data from the intervention and control districts. The primary outcome was the change in TB notifications during the intervention period compared with historical and control notifications. Results Over the 12-month intervention period, 15,669 people with TB were reported from 2,943 pharmacies in four districts. Among the people identified, 88% were male (n = 13,673), 95% had pulmonary disease (n = 14,969), and 4,256 (27%) were bacteriologically confirmed. Chain pharmacies (n = 14) contributed to 39% of the yield. TB notifications increased by 17,462 (+ 34%) over the baseline period compared with an 8% increase in the control districts. The number of bacteriologically confirmed notifications increased by 32% compared with 16% in the control districts. The proportion of bacteriological confirmation was similar before and during the intervention. Conclusion The results of the largest TB intervention with pharmacies globally showed incredible potential to link people with TB who are receiving care in the private sector. Mapping TB medicine sales in the private sector with tailored interventions can contribute to closing the gap in notifications where anti-TB drug sales in the private sector are prevalent.